Physicochemical and Mechanical Characterization of Raffia vinifera Pith - N. R. Sikame Tagne; T. E. Mbou; O. Harzallah; D. Ndapeu; W. Huisken; D. Nkemaja; E. Njeugna; M. Fogue; J-Y. Drean (Advances in Materials Science and Engineering)
In this paper, the physicochemical and mechanical properties of Raffia vinifera pith (RVP) are discussed. Microscopic observations have shown that the structure of the RVP is similar to that of a composite consisting of natural fibers. The effective area ratio of Raffia vinifera (RV) fibers was evaluated along the raffia stem using ImageJ software, and it decreases from the periphery to the center. Energy dispersion spectrometer (EDS) analysis shows that RVP is essentially composed of carbon and oxygen. Densities of RVP and its matrix were determined using Archimedes’ principle and law of mixtures, respectively; from the results obtained, they can be considered as one of the lightest materials. Young’s modulus of RVP has been obtained from tensile and bending tests, while that of matrix has been obtained using the law of mixtures during tensile tests. RVP has better specific properties, and the results of the matrix properties show that we can easily select another matrix which has better properties than the case studied during the elaboration of composites.